An Assessment and Comparative Study of Modern Thermal Insulation Systems - Alena Tažiková (TEM Journal, 2018)
The thermal protection and overall energy performance of a building are influenced by the gradual development of technical and energy requirements. This should be adapted into application of new thermal insulation materials and systems in construction. The paper deals with unconventional thermal insulation materials and systems that are mostly applied in buildings included in Modern Methods of Construction (MMC). Five types of thermal insulation systems or materials - Baumit openTherm, Knauf SMARTwall N C1, SATSYS ThermoUm, Knauf TP 435 B, and Aerogel Spaceloft - are assessed and compared to each other in a case study of a family house. Based on the comparison of the thermal insulation systems through multi-criteria decision-making method PATTERN, a significance ranking of the systems from construction cost, construction time, thermal conductivity, diffusion resistance and fire resistance point of view is determined.